In vitro testing of basal cytotoxicity: Establishment of an adverse outcome pathway from chemical insult to cell death. (March 2017) - Vinken, Mathieu; Blaauboer, Bas J.
Abstract: In this paper, an in vitro basal cytotoxicity testing strategy is described for new chemical entities that lack any pre-existing information on potential toxicity. Special attention is paid to the selection of the cellular system, cytotoxicity assay and exposure conditions. This approach is based on a newly proposed generic adverse outcome pathway from chemical insult to cell death that consists of 3 steps, including initial cell injury, mitochondrial dysfunction and cell demise. The suggested strategy to consider in vitro basal cytotoxicity as a first step in evaluating the toxicity of new chemical entities can be placed in a tiered strategy that could be continued by evaluating more specific types of toxicity. Highlights: A generic adverse outcome pathway from chemical insult to cell death is established. An in vitro basal cytotoxicity testing strategy is proposed. The proposed strategy highly contributes to the implementation of the 3Rs.